Hepatitis B and the Infected Health Care Worker: Public Safety at What Cost?. (2012) - Bhat, Mamatha; Ghali, Peter; Deschenes, Marc; Wong, Philip
Abstract : Public safety and the right of the health care worker to practise without prejudice based on underlying illness may be at odds for those affected by the hepatitis B virus (HBV). Nevertheless, HBV does not preclude entry into a health care profession, and the risk of transmission from health care worker to patient is not uniform across the spectrum of health care fields. In the present article, the authors present an overview of the literature regarding transmission of HBV from the health care worker to the patient, and the current recommendations that vary from province to province within Canada. The establishment of national guidelines to standardize monitoring of HBV infection among health care workers would improve health care work-place safety and patient care.